2019
DOI: 10.1002/ajim.22964
|View full text |Cite
|
Sign up to set email alerts
|

Dissecting the effect of workplace exposures on workers’ rating of psychological health and safety

Abstract: ObjectivesTo validate the factor structure of the Copenhagen Psychosocial Questionnaire (COPSOQ) in a North American population and dissect the associations between psychosocial factors and workplace psychological health and safety.MethodsConfirmatory factor analysis and multivariate linear regression were used to determine the associations between COPSOQ dimensions and a global rating of workplace psychological health and safety. Models were stratified by sex, gender roles, and age.ResultsThe COPSOQ factor st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 36 publications
0
19
0
3
Order By: Relevance
“…We found a corresponding pattern with the same groups most exposed to conflicts and offensive behaviours. An additional comparison revealed that business owners scored statistical significantly higher for the outcome dimensions Work Engagement (77) and Job Satisfaction (72), and lower for Stress (31) and Burnout (31) than the study sample did (results not shown in table). Table 4 displays psychometric characteristics for major occupational groups based on the ISCO-08 classification.…”
Section: Resultsmentioning
confidence: 80%
See 1 more Smart Citation
“…We found a corresponding pattern with the same groups most exposed to conflicts and offensive behaviours. An additional comparison revealed that business owners scored statistical significantly higher for the outcome dimensions Work Engagement (77) and Job Satisfaction (72), and lower for Stress (31) and Burnout (31) than the study sample did (results not shown in table). Table 4 displays psychometric characteristics for major occupational groups based on the ISCO-08 classification.…”
Section: Resultsmentioning
confidence: 80%
“…As it is adapted to the Swedish context, it differs from the international version of COPSOQ III, which showed satisfactory basic psychometric properties in findings from 6 countries (including data collected at Swedish workplaces) [5,30]. The factor structure of the mandatory "core" items defined for COPSOQ III has been validated in Canada [31] and the COPSOQ III domain for Social Capital has been validated by qualitative and quantitative methods in Sweden [10,32].…”
Section: Introductionmentioning
confidence: 99%
“…The overall structure of the questionnaire has previously been developed using factor analyses [2,3]. In two cases, this has already been performed regarding the present version [78,79], although additional studies are needed. Other aspects of construct validity should be tested.…”
Section: Discussionmentioning
confidence: 99%
“…We do not think the poor model fit statistics observed in our study are specific to the EKOS panel or the Canadian labour force. For example, previous CFA examinations of the 19 dimensions contained within the Copenhagen Psychosocial Environment Questionnaire (COPSOQ), using the same panel for recruitment, have demonstrated good model fit (Ramkissoon et al 2019 ). In addition, the high correlations between dimensions captured in the GM@W survey have been noted in a report from a Portuguese sample (Magalhães and Paul 2017 ), while the inability of the GM@W survey to reflect the 13 dimensions of The Standard has also been noted among a Canadian sample in a conference abstract (MacLellan et al 2016 ).…”
Section: Discussionmentioning
confidence: 99%